Wind turbine technology - Jha, A. R. (CRC Press, 2011)
Presents an introduction to the wind turbine technology, which can generate electrical energy with lower costs and zero greenhouse effects. Highlighting limitations, capabilities, and benefits, this text identifies the critical components of a wind turbine and describes the functional capabilities of each component.